(untitled) (Journal of Organizational Psychology, 2020)
Emotional Intelligence (EI) has been found to be an important aspect of individual and organizational success. To date, much of the effort to develop EI has emphasized workplace training and career development. We suggest that institutions of higher education (colleges and universities) can play an important role in the development of EI by incorporating various techniques and methodologies into educational processes, pedagogy, and curricula. A review of the literature on EI development is aligned with development opportunities in the higher education setting. Recommendations for implementing EI as part of the higher education experience are presented and discussed.